Chemical kinetics : from molecular structure to chemical reactivity - Arnaut, Luis G., 1960- (Elsevier, 2007)
Chemical Kinetics bridges the gap between beginner and specialist with a path that leads the reader from the phenomenological approach to the rates of chemical reactions to the state-of-the-art calculation of the rate constants of the most prevalent reactions: atom transfers, catalysis, proton transfers, substitution reactions, energy transfers and electron transfers. For the beginner provides the basics: the simplest concepts, the fundamental experiments, and the underlying theories. For the specialist shows where sophisticated experimental and theoretical methods combine to offer a panorama of time-dependent molecular phenomena connected by a new rational. Chemical Kinetics goes far beyond the qualitative description: with the guidance of theory, the path becomes a reaction path that can actually be inspected and calculated. But Chemical Kinetics is more about structure and reactivity than numbers and calculations. A great emphasis in the clarity of the concepts is achieved by illustrating all the theories and mechanisms with recent examples, some of them described with sufficient detail and simplicity to be used in general chemistry and lab courses. * Looking at atoms and molecules, and how molecular structures change with time. * Providing practical examples and detailed theoretical calculations * Of special interest to Industrial Chemistry and Biochemistry.